Strategi Guru Pendidikan Agama Kristen dalam Menerapkan Model Pembelajaran PAKEM - Felia Limbong; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Transformasi Indonesia, 2022)
Abstract: In the continuity of teaching and learning activities, it is adjusted to the learning model that has been designed by the previous teacher. However, in practice the learning model applied by the teacher remains the same at every meeting so as to create a bored atmosphere for students, students' interest in learning becomes less and there is no forum for students to channel their potential and abilities. Meanwhile, a quality and quality education system depends on learning activities that take place in a challenging and interesting way for students. In response to this, it is necessary to have a variety of classroom management strategies by applying the PAKEM model. This study aims to examine how the strategy of PAK teachers in implementing the PAKEM model. The study used a descriptive qualitative approach with a literature review. Then, the results of this study, that the strategy of PAK teachers in applying the PAKEM model in learning Christian Religious Education can be done by designing learning activities that imitate Jesus' strategy in teaching and also by designing learning activities that involve students as a whole and can encourage students to play an active role. in participating in learning and can give a good impression to students and also to develop the potential in students.Keyword: PAK Teacher Strategy, PAKEM Model, Christian Religious EducationAbstrak: Dalam keberlangsungan kegiatan belajar mengajar disesuaikan dengan model pembelajaran yang telah di rancang oleh guru sebelumnya. Namun, dalam pelaksanaannya model pembelajaran yang diterapkan oleh guru tetap sama pada setiap pertemuan sehingga menciptakan suasana yang bosan bagi siswa, minat siswa dalam belajar menjadi kurang dan tidak adanya wadah bagi siswa dalam menyalurkan potensi dan kemampuannya. Sementara, sistem pendidikan yang bermutu dan berkualitas tergantung pada kegiatan pembelajaran yang berlangsung dengan menantang dan menarik bagi siswa. Dalam menanggapi hal ini, diperlukan adanya strategi pengelolaan kelas yang bervariasi dengan menerapkan model PAKEM. Penelitian ini bertujuan dalam mengkaji bagaimana strategi guru PAK dalam menerapkan model PAKEM. Penelitian tersebut menggunakan pendekatan kualitatif deskriptif dengan tinjaun pustaka. Kemudian, hasil dari penelitian ini, bahwa strategi guru PAK dalam menerapkan model PAKEM dalam pembelajaran Pendidikan Agama Kristen dapat dilakukan dengan merancang kegiatan pembelajaran yang meneladani strategi Yesus dalam mengajar dan juga dengan merancang kegiatan pembelajaran yang melibatkan siswa secara utuh serta dapat mendorong siswa untuk berperan aktif dalam mengikuti pembelajaran dan dapat memberi kesan yang baik bagi siswa dan juga untuk mengembangkan potensi-potensi dalam dirinya siswa.Kata Kunci: Strategi Guru PAK, Model PAKEM, Pendidikan Agama Kristen